2020
DOI: 10.1002/ptr.6829
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin induces ferroptosis by inhibiting gamma‐glutamyl cycle in TE1 cells

Abstract: Oridonin (Ori) is a natural tetracyclic diterpenoid active compound with excellent antitumor activity, but the mechanism of Ori on esophageal cancer cell, TE1, remains unclear. In this study, we examined the levels of intracellular iron, malondialdehyde, and reactive oxygen species after Ori treatment, while interfering with the effects of Ori with ferroptosis inhibitor, demonstrating that Ori's inhibition of TE1 cell proliferation is associated with ferroptosis. To understand the molecular mechanism of Ori, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…To obtain this cysteine, GSH must be catabolized. GSH export and extracellular catabolism via the gamma-glutamyl cycle does contribute to intracellular cysteine pools [72], and disruption of the key enzyme gamma-glutamyl transpeptidase 1 (GGT1) may be sufficient to induce ferroptosis [73]. However, this is likely to be only useful in the short-term.…”
Section: Why Is Cysteine Even Essential?mentioning
confidence: 99%
“…To obtain this cysteine, GSH must be catabolized. GSH export and extracellular catabolism via the gamma-glutamyl cycle does contribute to intracellular cysteine pools [72], and disruption of the key enzyme gamma-glutamyl transpeptidase 1 (GGT1) may be sufficient to induce ferroptosis [73]. However, this is likely to be only useful in the short-term.…”
Section: Why Is Cysteine Even Essential?mentioning
confidence: 99%
“…Under such conditions, GPX4 might employ alternative reducing molecules, like cysteine and its metabolite CoA [165,175]. Glutathione catabolism [176], compared to the RTP [177], may be a more efficient alternative source of cysteine to avoid ferroptosis, at least in short-term cysteine deprivation. The CoAdependent post-translational modification, named CoAlation [178], of glycolytic enzymes may boost NADPH synthesis via the PPP, affording protection from ferroptosis [179].…”
Section: Cysteine Is Preventive Of Ferroptosis and Promoter Of Cell S...mentioning
confidence: 99%
“…To investigate the underlying mechanism, a UPLC-MS/MS-based metabolomics analysis of TE1 cells was conducted. It was found that oridonin administration altered the levels of glutamate, 5-oxoproline, and gamma-glutamyl amino acids (gamma-glutamyl valine and gamma-glutamyl leucine), which could suppress the gamma-glutamyl cycle to induce ferroptosis to exert its anti-EC activity ( Zhang et al, 2021 ).…”
Section: Applications Of Metabolomics For Medicinal Plants In Gastroi...mentioning
confidence: 99%